Method of acetylation of cellulose nanofibers. - Harun, Jalaludin; Md. Tahir, Paridah; Jonobi, Mehdi; Al-Edrus, Syeed Saiful Azry Osman (2010)

(untitled)
The present invention relates to a method of acetylation of cellulose fibers, wherein pulped fibers are acetylated, the acetylated fibers are processed to acetylated nanofibers and subsequently the acetylated nanofibers are isolated. The method of the invention provides a novel processing route to produce cellulose nanofibers with more hydrophobic surfaces.